Republic of Haiti - Towards Greater Fiscal Sustainability and Equity : A Discussion of Public Finance - World Bank (Washington, DC, 2015)
Haiti has a vision to become an emerging economy by 2030. Haiti has comparative advantages, including its proximity and access to major markets; a young labor force and a dynamic diaspora; and substantial geographic, historical, and cultural assets. Areas of economic opportunity for Haiti include agribusiness, light manufacturing, and tourism. Recognizing these opportunities, the Government of Haiti issued in May 2012 a strategic development Plan (PSDH), aiming at building a new modern, diversified, resilient, competitive, and inclusive economy, respectful of its environment and in which people’s basic needs is met. This report examines more particularly how to: (i) mobilize greater fiscal revenue; (ii) enhance the growth dividend of public investment; (iii) improve the efficiency of spending in critical sectors such as health, education, and social protection; and (iv) protect the budget from a return of fuel price subsidies. This report builds on newly available data, including the 2012 household survey, the 2012 demographic and health survey (DHS), and the 2011-12 school census, to provide a better understanding of the equity and sustainability issues in the delivery of some basic services such as health and education, and engage policy makers and other actors on gaps and priorities.